Microbial degradation of pyridine: a proposed nitrogen metabolism pathway deciphered in marine mangrove Bacillus aryabhattai strain NM1-A2 - Muhammad Kashif; Lirong Bai; Jianwen Xiong; Shuming Mo; Yimeng Sang; Kunmei Huang; Jingjing Song; Syed Jalil Shah; Sohail Khan; Taj Malook Khan; Chengjian Jiang (Chemical and Biological Technologies in Agriculture, 2023)
Abstract Background Diverse microbes, such as bacteria, are of immense worth to mangrove ecosystems due to their adaptability to salinity and variable environmental characteristics conditions. Pyridine and its derivatives compose most heterocyclic aromatic compounds largely produced by human activities that lead to environmental pollution. Bacteria have a crucial role in the nutrient cycling of carbon and nitrogen etc., to understand their functional involvement with environmental factors or ecosystem functioning as well as the species invasion and domestic or agriculture pyridine degradation pollution activities that threaten the mangrove ecosystem. Methods This work established the genetic-based molecular degradation of organic compounds in the mangrove ecosystem, which ultimately makes the availability of nutrients. As well as the effects of various abiotic factors on pyridine degradation to discover the pyridine degradation and the removal of ammonia nitrogen and the proposed nitrogen metabolism pathway. Results The novel bacterial strain NM1-A2 was isolated from mangrove sediments and, after 16S rRNA gene sequence analysis identified as Bacillus aryabhattai. NM1-A2 completely degraded pyridine within a 100 h incubation period at a temperature of 35 °C, an initial pH of 7.0, glucose and a pyridine concentration of 500 mg/L. The pseudo-first-order kinetics model described the pyridine biodegradation profile of NM1-A2 well. Interestingly, within 96 h the strain achieved almost complete pyridine degradation with a total organic carbon (TOC) removal of 87.9% ± 0.19% (from 377.52 ± 6.9 mg/L to 45.65 ± 0.14 mg/L). Within 96 h, the pyridine ring in the total nitrogen (TN) fraction at the maximum concentration of 55.31 ± 0.17 mg/L, furtherly 51.3% ± 2.39% of (TN) converted into Ammonia nitrogen (NH4 +-N). Furthermore, NM1-A2 exhibited its pyridine biodegradation activity decreased by only 4% after three consecutive cycles (48 h each). Moreover, NM1-A2 possessed nrt-ABCD nitrate transport family and gltABCD operons that participate in the activities of glutamine and glutamate synthetase in NH4 + conversion in the nitrogen cycle. Furthermore, the nitrogen metabolism genes (nrtA, nrtB, nrtC, nirB, nirD, gltB, gltD, glnA) exhibited expression in NM1-A2. Conclusion This research offers a potential treatment strategy for pyridine degradation in the mangrove ecosystem. Graphical Abstract